Analisis Penetapan Kelayakan Agunan Dalam Penyaluran Pembiayaan Murabahah Ditinjau Dari Manajemen Risiko Bank Syariah (Studi Kasus Pada BPRS Rahma Syariah Kediri) - Ayu Sifaul Muzariah (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2022)
Islamic financial institutions in Indonesia are currently developing so rapidly, especially murabaha financing, therefore each distribution of murabahah financing must first be analyzed for the feasibility of the collateral by the risk management of Islamic banks. The purpose of this study was to determine how the analysis of the determination of the feasibility of collateral in the distribution of murabahah financing in terms of risk management of Islamic banks at BPRS Rahma Syariah Kediri. This research uses qualitative research with descriptive analysis. The results of this study indicate that the most collateral provided by customers is in the form of Certificate of Ownership (SHM) and Proof of Ownership of Motorized Vehicles (BPKB). BPRS Rahma Syariah Kediri in determining the eligibility of collateral based on criteria of economic value, undamaged goods, marketable, and legally binding. The determination of the feasibility of collateral carried out by BPRS Rahma Syariah Kediri is also carried out by the risk management of Islamic banks, namely the risk identification process, risk measurement process and risk monitoring process. For the settlement of problematic murabahah financing, the risk management of Islamic banks is carried out by restructuring, settlement through collateral and also book write-off. Keywords: Collateral, Murabaha Financing, Islamic Bank Risk Management